Women doctors in female urology: current status and implications for future workforce. Issue Volume 128:Issue Supplement 1(2021) (2nd August 2021) - Pirpiris, Athina; Chan, Garson; O'Connell, Helen E.; Gani, Johan
Abstract : Objective: To objectively determine the percentage of female trainees and consultants who are interested in their career being focussed on female urology (FU) in order to facilitate the improved planning for the future of this sub‐specialty. Subjects and methods: This was an international cross‐sectional study spanning 1 year, from December 2018 to December 2019. An anonymous, voluntary survey was generated using the online survey generator Survey monkey ® . The survey was sent to urology consultants and trainees who were female from Australia, New Zealand, and Canada. Results: The total response rate to the survey was 61%. Up to 50% of female consultants and trainees selected a career in FU due to their gender, but up to 75% of respondents were also interested in FU of their own accord. Common concerns held by a majority of respondents included both the medical community's and the public's lack of awareness of FU as a component of urological expertise. Despite these concerns, most of the trainees were not concerned regarding their future work opportunities in FU, and many had intentions to pursue a fellowship in FU. Conclusion: Female urology is an increasingly popular sub‐specialisation of urology, given the steady increase in the intake of female trainees. Similar trends were identified internationally. Urology training in this area will need to continue to increase the community's and the primary health care referrer's awareness in order to ensure the continued success and growth of the sub‐specialty.